Copper nickel alloy nanorods textured nanoparticles for oxygen evolution reaction. (10th February 2020) - Kumar, Mohit; Jeong, Dong In; Yoon, Dae Ho
Abstract: Facile and low-cost synthesis routes of highly competent catalyst materials for applications in oxygen evolution reaction are imperative. In this work, we synthesised bimetallic alloy crystals using nickel nitrate as a metal ions source and trimesic acid as an organic linker. Further annealing at an elevated temperature under a nitrogen atmosphere yielded alloy nanorods textured nanoparticles. Numerous characterization techniques were used, revealing the bimetallic nature of the synthesised product. The product was a highly efficient and stable material for oxygen evolution reaction (OER) in an alkaline medium. In 1.0 M KOH solution, the copper nickel alloy with graphitic carbon (Cu3.8 Ni@C) catalyst showed remarkable OER activity, obtaining an overpotential of 233 mV at a current density of 10 mA cm −2 with stability up to 18 h under continuous electrolysis. Consequently, we believe that this work could contribute insights into low-cost electrocatalysts for OER.